Dinosaur explorers. #7, Cretaceous craziness - Slaium; Albbie (Comic writer) (Papercutz, 2020)
Emily, Rain, and Stone and their fellow lost-in-time Dinosaur Explorers are itching to check out the Cretaceous period, a time in which the continents were splitting apart and many new and varied dinosaur species. With all the new ecological niches forming from the landmass splits, these dinosaurs have a lot of expanding and exploring to do.